Immune control of HIV-1 after early treatment of acute infection. - Rosenberg, E; Altfeld, M; Poon, S; Phillips, M; Wilkes, B; Eldridge, R; Robbins, G; D'Aquila, RT; Goulder, P; Walker, B (2000)
Virus-specific T-helper cells are considered critical for the control of chronic viral infections. Successful treatment of acute HIV-1 infection leads to augmentation of these responses, but whether this enhances immune control has not been determined. We administered one or two supervised treatment interruptions to eight subjects with treated acute infection, with the plan to restart therapy if viral load exceeded 5,000 copies of HIV-1 RNA per millilitre of plasma (the level at which therapy has been typically recommended) for three consecutive weeks, or 50,000 RNA copies per ml at one time. Here we show that, despite rebound in viraemia, all subjects were able to achieve at least a transient steady state off therapy with viral load below 5,000 RNA copies per ml. At present, five out of eight subjects remain off therapy with viral loads of less than 500 RNA copies per ml plasma after a median 6.5 months (range 5-8.7 months). We observed increased virus-specific cytotoxic T lymphocytes and maintained T-helper-cell responses in all. Our data indicate that functional immune responses can be augmented in a chronic viral infection, and provide rationale for immunotherapy in HIV-1 infection.